Online video maker / Azlina Mohd Mydin, Wan Anisha Wan Mohammad and Rafizah Kechil - Mohd Mydin, Azlina Mohd Mydin; Wan Mohammad, Wan Anisha; Kechil, Rafizah (Unit Penerbitan dan Publisiti JSKM, 2022)
1. Filmora - Software that can easily explore to create video content 2. Clipchamp - Online application that allow to create and edit video including screen recording and have application of text to speech 3. Kapwing - Online application that allow to create and edit video but have limitation of time (if free version)